Experience With Unfavorable Iliac Access When Performing Fenestrated/Branched Endovascular Aneurysm Repair. (April 2021) - Hertault, Adrien; Bianchini, Aurélia; Daniel, Guillaume; Martin-Gonzalez, Teresa; Sweet, Birgit; Sgorlon, Giada; Fabre, Dominique; Sobocinski, Jonathan; Haulon, Stéphan
Purpose: To review a single-center experience with fenestrated and branched endovascular aneurysm repair (f/bEVAR) in patients with challenging iliac anatomies. Materials and Methods: A retrospective review of the department's database identified 398 consecutive patients who underwent complex endovascular repair f/bEVAR between January 2010 and June 2018; of these, 67 had challenging accesses. The strategies implemented to overcome access issues were reviewed, using a dedicated scoring system to evaluate the access (integrating diameter, tortuosity, calcification, and previous open or endovascular repair). Results: In this subgroup of patients, the most common graft design was a 4-vessel fenestrated endograft (27, 40.3%). Hostile access was due to small diameter (<7 mm) in 25 patients (37.3%) and/or concentric calcifications in 19 patients (26.9%). Mean iliac diameter was 5.5±2.6 mm on the right side and 6.0±2.5 mm on the left side. Previous open or endovascular aortoiliac repair had been performed in 15 patients (22.4%), and 20 patients (29.9%) had a stent previously implanted in at least 1 iliac artery, resulting in the inability to perform standard fenestrated repair with access from both sides. Five patients (7.5%) had a single patent iliac access. Eight distinctive strategies were identified to overcome these access issues, including the use of preloaded renal catheters in the endograft delivery system, angioplasty, graft modification (branches instead of fenestrations or 4 preloaded fenestrations), a conduit via a retroperitoneal approach, iliac artery recanalization, and/or the multiple puncture technique. Technical success was achieved in 62 cases (92.5%). Four patients had access complications and 1 died in the early postoperative period of multiorgan failure. Median follow-up was 24.6 months (IQR 7.2, 41.3). Clinical success at the end of follow-up was achieved in 57 patients (85.1%). During follow-up, 14 patients died, including 4 from an aorta-related cause. Conclusion: Dedicated strategies can be implemented to overcome hostile iliac access in patients with complex aneurysms when f/bEVAR is required. Typically, these maneuvers are associated with favorable outcomes.